The Impact of Beauty Influencer Marketing on Brand Evangelism on TikTok - Rania, Alya Shidqa; Hasan, Zidny Ilma (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Social media has become a valuable media to market a product or service, whereby influencers play a key role as opinion leaders. Key opinion leaders play an important role for brands as they have the ability to drive their audience into becoming consumers. This study aims to explore the impact of influencer marketing strategy on brand evangelism, which includes recommending brands and defending them from criticism. Influencer marketing strategies are measured through influencer engagement rate, content relevance, influencer authenticity, audience reach, campaign frequency, and consumer sentiment. Using a quantitative approach, this study applies the Partial Least Square Structural Equation Modeling (PLS-SEM) technique with the use of SmartPLS4. Data were collected from 190 people in the range of Generation Z, who follow Tasya Farasya on TikTok, and had purchased either OMG Beauty foundation, cushion, or two-way cake products in the last six months based on her recommendation. The findings show that influencer engagement rate, content relevance, audience reach, campaign frequency, and consumer sentiment have a positive impact on brand evangelism. However, influencer authenticity has no significant impact on brand evangelism. These findings provide a better understanding of the role of influencers in driving brand evangelism and offer practical insights to develop more effective marketing strategies